Analisis Pengaruh Suhu Panel Surya Terhadap Output Panel Performance - Jaya, Harie Satiyadi; Rahmat, Muhamad Hudan; Asrori, Asrori (Journal of Mechanical Engineering, 2024)
The main obstacle that greatly affects solar power output systems is the low conversion efficiency of solar panels, which is greatly influenced by their operating temperature. Failure to consider solar panel temperature increases the financial risks of installing the installation system. In this research, the output performance of solar panels was examined in outdoor conditions. All data was measured and recorded from 09.00 to 17.00, over 30 minute intervals. Panel temperature measurements were carried out using a Ditec C355 infrared thermometer. And then compared with using Pvsyst software. The output power of a solar panel is highly dependent on the solar radiation that falls on its surface. The amount of incoming sunlight is much higher during the hours from 11.00 to 13.00, which can be determined as the peak of the sun during the day. So it can be concluded that the ideal climate for setting up a large solar installation system is a cool and sunny climate.